Modification of Traditional Balinese Food as Disaster Emergency Food - Ni Putu Agustini; I Gusti Putu Sudita Puryana; I Komang Agusjaya Mataram (JURNAL NUTRISIA, 2022)
This study aimed to make disaster formula food based on traditional Balinese local food quality, nutritious, safe and in accordance with Balinese culture so that it can be accepted to cope with food availability in a state of disaster. The development of the disaster formula is based on the traditional Balinese jaja satuh meal made from glutinous rice flour and brown sugar with the substitution of treatment using green beans powder, peanuts, and cashews as a source of protein, and Moringa leaf powder as a source of food fiber. The study was designed in a randomized block design with six formulations and three replications. The results showed that the selected treatment of the formulation was F4 (20 g glutinous rice flour, 25g peanut powder, 5 g Moringa leaf powder, and 50 g brown sugar) with a degree of preference for color, aroma, texture, taste and overall acceptance of the like value.This formula has a water content of 7.18%, ash 1.34%, protein 16.41%, fat 13.53%, carbohydrates 61.48%, food fiber 18.87%, Fe 6.23 ppm and total energy of 433.27 per 100 gram formula. This formula is microbiologically safe with a shelf life more than 10 days. One portion of Balinese traditional local food-based disaster formula as much as 50 g can contribute energy of 216.64 kcal (10.31%), protein 8,205 g (16.41%), and fat 6.765 g (16.91%) for the standard emergency food is 2100 kcal, 50 g protein and 40 g fat.